Isolation and selection of bacteria strains with high dimethoate (organophosphorus pesticide) decomposing activity - Le Ha, Pham Thi; Thuy, Tran Thi; Hang, Nguyen Duy; Mua, Le Tat (Academia Journal of Biology, 2015)
Four strains of bacteria, isolated from the agricultural soil of Da Lat city, were capable to grow on the mineral medium with 50 mg dimethoate/ml. The effects of the concentration of dimethoate and of the pH on the growth and decomposing activity of these strains were determined. Cultured at the concentration of 50 mg dimethoate/ml and the pH 7, the strains T and C have the biggest dry biomass.